Neuraxial Anesthesia and Lower Extremity Peripheral Nerve Blocks for Ankle Surgery in a Patient With Chronic Inflammatory Demyelinating Polyneuropathy: A Case Report. Issue 2 (15th January 2020) - Wells, Ashley V.; Akerman, Michael; Weinberg, Roniel Y.
Abstract : Chronic inflammatory demyelinating polyneuropathy (CIDP) is a rare autoimmune disease that targets the peripheral nervous system. The literature on the use of regional anesthesia in CIDP is limited. We report a patient with CIDP who received a combined spinal-epidural (CSE) and saphenous and popliteal peripheral nerve blocks (PNBs) for ankle surgery. The CSE and PNBs resolved without incident. On approximately the fourth postoperative day, the patient reported a worsening of baseline CIDP symptoms in all extremities. Given the diffuse presentation, the CIDP exacerbation was attributed to the perioperative stress response. The exacerbation improved by 4 months postoperatively.